Pengabdian Masyarakat: Konsultasi TPA Dengan Pemohon PBG Menara Telekomunikasi 72 Meter Di Dusun Pasir Pandak Desa Kepenuhan Timur Kabupaten Rokan Hulu Provinsi Riau - Purwo Subekti; Bambang Edison; Anton Ariyanto; Taufik Kurniawan; Januar Kaswari; Armadani (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to enhance partners' understanding of the technical requirements and regulatory framework governing the Building Approval (Persetujuan Bangunan Gedung/PBG) process for the construction of a 72-meter telecommunication tower in Dusun Pasir Pandak, Kepenuhan Timur Village, Rokan Hulu Regency, Riau Province. The partners involved were PT. XX as the applicant and the Department of Housing and Settlement of Rokan Hulu Regency as the technical authority responsible for evaluating the application documents. The implementation methods included technical consultations, document reviews, technical discussions, and continuous assistance based on the prevailing laws and regulations. The consultation results indicated that several technical documents required improvement, particularly regarding the specifications of the lightning protection and grounding systems, as well as the adjustment of the safety radius to 125% of the proposed tower height in accordance with the recommendations of the Expert Professional Team (Tim Profesi Ahli/TPA). The assistance program successfully improved the partners' understanding of the technical documentation required for Building Approval, strengthened inter-agency coordination, and accelerated the document revision process. This activity is expected to support the issuance of Building Approval that complies with safety standards, structural reliability requirements, and applicable regulations, thereby ensuring that the telecommunication tower construction can be carried out safely, efficiently, and sustainably.